Australia’s tertiary education system – challenges and perspectives in the context of the operation of the church tertiary system - Casamento , Antohony (Prawo Kanoniczne, 2024)
Catholic higher education in Australia operates in a complex landscape. This paper explores the place of Catholic universities within the Australian higher education sector and the challenges associated with them. It examines the tension between maintaining an authentic Catholic identity as understood through Ex Corde Ecclesia whilst also adhering to secular laws such as those pertaining to gender identity and staff recruitment. The paper also presents the opportunity for government support of faith-based education, highlighting strategies to uphold core Catholic beliefs as well as continuing a mission of social justice. Moving forward, Catholic universities are encouraged to proudly uphold their Catholic identity, grounded in the confidence of the Gospel and the hope it brings. They must resist the temptation to dilute the transformative power and beauty of Catholic teachings simply for the purpose of making them more contemporary or appealing. Catholic higher education institutions are unique from other universities in their emphasis on building a community grounded in kindness and mercy and make a tangible difference in society. With the support of the Australian Government, Catholic institutions can continue to provide a holistic education that not only imparts knowledge, but also fosters an authentic religious identity and mission that prepares students to contribute to the common good within and of their communities